Linking microbial communities, functional genes and nitrogen-cycling processes in forest floors under four tree species. (December 2016) - Ribbons, Relena R.; Levy-Booth, David J.; Masse, Jacynthe; Grayston, Sue J.; McDonald, Morag A.; Vesterdal, Lars; Prescott, Cindy E.
Abstract: Tree species can influence rates of soil N transformations, but the question remains whether differences in N cycling rates are mirrored by the abundance of relevant functional genes. We studied whether the influence of tree species on soil N transformation processes and abundance of functional genes exist across two sites in British Columbia with different N availability. We used the 15 N pool-dilution method to estimate gross rates of ammonification and nitrification in forest floors of four conifers in a common garden experiment. The abundances of bacteria, fungi, nitrification (AOA amoA, AOB amoA ) and denitrification ( nirS, nirK ) genes were determined by qPCR. Western red cedar ( Thuja plicata) had the highest rates of gross ammonification and NH4 + consumption, followed by Sitka spruce ( Picea sitchensis), hemlock ( Tsuga heterophylla), and Douglas-fir ( Pseudotsuga menziesii) ; all species showed net nitrate immobilization. Western red cedar forest floors had the greatest abundance of bacterial 16S genes and ammonia-oxidizing archaea amoA genes. This suggests that tree species foster different abundances of ammonification and denitrification functional groups. Differences in N transformation rates between the sites were related to site N status, as reflected in C:N ratios of the forest floor and microbial biomass, and were more closely tied to rates of N consumption rather than gross mineralization. Rates of most N transformation processes were related to microbial C:N ratio, indicating that the N status of microbes rather than their biomass or activity level determined the rates of N cycling. Ammonification rates were associated with forest floor and microbial biomass C:N ratio as well as bacterial and fungal abundances. Nitrification rates and denitrification gene abundance were associated with microbial biomass C:N ratios and AOA amoA gene abundance. The forest floor's genetic potential for denitrification was positively correlated with its nitrification potential as indicated by ammonia-oxidizer abundance. We conclude that tree species influenced forest floor N cycling and soil microbial gene abundances, and that functional genetics can be useful for exploring mechanistic links between tree species and nitrogen cycling processes. Highlights: Tree species influenced potential N cycling and soil microbial functional genes. Western red cedar had the highest rates of N cycling and 16S and amoA AOA. Tree species effects on N cycling were influenced by site nutrient status. Functional genes and 15N pool-dilution provide new insights to forest N cycling.